A Review of Existing Treatments for Substance abuse among the Elderly and Recommendations for Future Directions - Alexis Kuerbis; Paul Sacco (SAGE Publishing, 2013)
Background With population aging, there is widespread recognition that the healthcare system must be prepared to serve the unique needs of substance using older adults (OA) in the decades ahead. As such, there is an increasingly urgent need to identify efficient and effective substance abuse treatments (SAT) for OA. Despite this need, there remains a surprising dearth of research on treatment for OA. Aims of review This review describes and evaluates studies on SAT applied to and specifically designed for OA over the last 30 years with an emphasis on methodologies used and the knowledge gained. Methods Using three research databases, 25 studies published in the last 30 years which investigated the impact of SAT on OA and met specific selection criteria were reviewed. Results A majority of the studies were methodologically limited in that they were pre-to-post or post-test only studies. Of the randomized controlled trials, many were limited by sample sizes of 15 individuals or less per group, making main effects difficult to detect. Thus, with caution, the literature suggests that among treatment seeking OA, treatment, whether age-specific or mixed-age, generally works yielding rates of abstinence comparable to general populations and younger cohorts. It also appears that with greater treatment exposure (higher dosage), regardless of level of care, OA do better. Finally, based on only two studies, age-specific treatment appears to potentiate treatment effects for OA. Like younger adults, OA appear to have a heterogeneous response to treatments, and preliminary evidence suggests a possibility of treatment matching for OA. Conclusions Expansion of research on SAT for OA is urgently needed for maximum effectiveness and efficiency of the healthcare system serving these individuals. Future research needs to include laboratory and community based randomized controlled trials with high internal validity of previously vetted evidenced-based practices, including Motivational Interviewing, cognitive behavioral therapy, and medications such as naltrexone, to determine the best fit for OA.